Pengaruh Brand Image, Brand Luxury , Harga, Dan Desain Produk Terhadap Minat Beli Samsung Z Flip 5 Di Kota Semarang - Naim, Aulia Anin; Sedayu, Agung; Usman, Usman; Hariyadi, Guruh Taufan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This research aims to determine the influence of brand image, luxury brand, price, and product design on buying interest in the Samsung Z Flip 5 in Semarang City. This research uses primary data and quantitative methods. Researchers conducted a pre-survey on 30 respondents by distributing questionnaires, then after that the researchers conducted a survey by distributing questionnaires via Google Form to 150 respondents and processing the data using SmartPLS. From the results of data processing, it was found that brand image had a significant influence, luxury brand had no significant influence, price had a significant influence, and design had no significant influence on interest in purchasing Samsung Z Flip 5 smartphone products in Semarang City.  Keywords:  Brand Image ; Brand Luxury ; Price ; Design ; Purchase Intention